Serum CXCL1 Is a Prognostic Factor for Patients With Hepatitis B Virus–Related Acute-On-Chronic Liver Failure - Xiao, Lanlan; Tang, Shima; Zhang, Lingjian; Ma, Shanshan; Zhao, Yalei; Zhang, Fen; Xie, Zhongyang; Li, Lanjuan (Frontiers in Medicine, 2021)
Purpose: Neutrophils and cytokines play a major role in the pathogenesis of acute-on-chronic liver failure (ACLF). We aimed to determine whether chemokine (CXC) ligand 1 (CXCL1), a key marker of neutrophil recruitment and activation, could predict the severity and prognosis of hepatitis B virus–related ACLF (HBV-ACLF). Methods: Hospitalized patients with HBV-ACLF were enrolled in a prospective study and stratified as survivors (alive at 28 days) and nonsurvivors (deceased at 28 days). Serum CXCL1 levels were measured in healthy controls, patients with chronic HBV, patients with HBV-related compensated cirrhosis, and patients with HBV-ACLF. Univariate and multivariable logistic analyses, Pearson correlation analysis, area under the receiver operating characteristic curve (AUROC), and Z tests were used to evaluate the performance of CXCL1 as a marker in HBV-ACLF. Results: Patients with HBV-ACLF had significantly higher serum levels of CXCL1 and neutrophil count than healthy controls and patients with chronic HBV or HBV-related compensated cirrhosis (P < 0.01, respectively). Among patients with HBV-ACLF, survivors had lower serum CXCL1 levels and neutrophil count than those of nonsurvivors (P < 0.001, P < 0.05, respectively). Serum CXCL1 level was positively correlated with neutrophil count (r = 0.256, P = 0.001), ACLF grade (r = 0.295, P < 0.001) and organ failure, including coagulation (r = 0.21, P = 0.005) and brain failure (r = 0.198, P = 0.008). Multivariable logistic analyses showed serum CXCL1 (OR [95% CI] = 1.017 [1.009–1.025], P < 0.001) was an independent risk factor for 28-day mortality in HBV-ACLF. Meanwhile, the AUROC analysis demonstrated that serum CXCL1 (0.741 [0.669-0.804]) might be a reliable prognostic biomarker for patients with HBV-ACLF. Conclusions: Overall, serum CXCL1 can serve as a biomarker indicating the severity of disease and prognosis for patients with HBV-ACLF. CXCL1 might also be a therapeutic target in this disease.